Hemozoin Inhibition and Control of Clinical Malaria - Chibueze Peter Ihekwereme; Charles Okechukwu Esimone; Edward Chieke Nwanegbo (Hindawi Limited, 2014)
Malaria has a negative impact on health and social and economic life of residents of endemic countries. The ultimate goals of designing new treatment for malaria are to prevent clinical infection, reduce morbidity, and decrease mortality. There are great advances in the understanding of the parasite-host interaction through studies by various scientists. In some of these studies, attempts were made to evaluate the roles of malaria pigment or toxins in the pathogenesis of malaria. Hemozoin is a key metabolite associated with severe malaria anemia (SMA), immunosuppression, and cytokine dysfunction. Targeting of this pigment may be necessary in the design of new therapeutic products against malaria. In this review, the roles of hemozoin in the morbidity and mortality of malaria are highlighted as an essential target in the quest for effective control of clinical malaria.